2020
DOI: 10.1002/rcr2.554
|View full text |Cite
|
Sign up to set email alerts
|

Oesophagobronchial perforations after placement of an oesophageal self‐expanding metallic stent

Abstract: An oesophageal fully covered self‐expanding metallic stent (SEMS) was placed in a 54‐year‐old Japanese man to relieve dysphagia owing to a stage cT1bN3M1c lung adenocarcinoma. High expression of programmed cell death‐ligand 1 was microscopically confirmed, and pembrolizumab was subsequently administered. Several days later, the patient was hospitalized with septic shock, and severe mediastinitis and pneumonia caused by oesophageal SEMS‐induced oesophageal and bronchial perforations were observed. Thoracoscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…One report showed that one cycle of pembrolizumab caused tracheoesophageal fistula formation in a patient with squamous cell lung cancer and bronchial stent in the left bronchus [ 8 ]. Another study showed that one cycle of pembrolizumab caused esophagobronchial perforations after the placement of an esophageal self-expanding metallic stent in a patient with stage IV lung adenocarcinoma [ 9 ]. Based on the above considerations, we might be able to explain the process of fistula formation associated with ICIs ( Fig 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…One report showed that one cycle of pembrolizumab caused tracheoesophageal fistula formation in a patient with squamous cell lung cancer and bronchial stent in the left bronchus [ 8 ]. Another study showed that one cycle of pembrolizumab caused esophagobronchial perforations after the placement of an esophageal self-expanding metallic stent in a patient with stage IV lung adenocarcinoma [ 9 ]. Based on the above considerations, we might be able to explain the process of fistula formation associated with ICIs ( Fig 4 ).…”
Section: Discussionmentioning
confidence: 99%